Workshop on Strengthening TPACK in ESD-Based Science Learning in Implementing the Merdeka Curriculum [Workshop Penguatan TPACK pada Pembelajaran IPA Berbasis ESD dalam Implementasi Kurikulum Merdeka] - Dandan Luhur Saraswati; Riandi Riandi; Asep Kadarohman; Andi Suhandi; Achmad Samsudin; Rahmi Zulva; Any Fitriani; Taj Rosyidah; Rizki Maulana Ashidiq; Asep Supriatna (Jurnal Pengabdian Isola, 2023)
Education for Sustainable Development (ESD) empowers individuals to create a sustainable future, while the government needs policies and teachers' knowledge in integrating ESD in education, including technology with TPACK framework for learning efficiency. The main challenge for teachers is to integrate technology into learning by ensuring the suitability of technology as teaching material, content pedagogy, learning objectives, and subject matter character, and need to develop this ability on an ongoing basis to ensure success in achieving educational goals. So that the TPACK strengthening workshop on ESD-based science learning in implementing the Merdeka Curriculum as a form of answer to the above problems aims to train teachers' TPACK abilities in the teaching process through online workshops with the help of zoom meetings and offline. The method used involves structured workshops with various methods, such as lectures, demonstrations, questions and answers, and exercises to produce teacher best practice papers in using technology in learning. The results of this workshop have interesting implications for improving science teachers' understanding of the use of innovation in learning.Pendidikan untuk Pembangunan Berkelanjutan (ESD) memberdayakan individu untuk menciptakan masa depan berkelanjutan, sementara pemerintah membutuhkan kebijakan dan pengetahuan guru dalam mengintegrasikan ESD dalam pendidikan, termasuk teknologi dengan kerangka kerja TPACK untuk efisiensi pembelajaran. Tantangan utama bagi guru adalah mengintegrasikan teknologi ke dalam pembelajaran dengan memastikan kesesuaian antara teknologi sebagai bahan ajar, pedagogi konten, tujuan pembelajaran, dan karakter materi pelajaran, serta perlu mengembangkan kemampuan ini secara berkelanjutan untuk memastikan kesuksesan dalam pencapaian tujuan pendidikan. Sehingga workshop penguatan TPACK pada pembelajaran IPA berbasis ESD dalam  implementasi Kurikulum Merdeka sebagai salah satu bentuk jawaban atas permasalahan diatas bertujuan untuk melatih kemampuan TPACK guru dalam proses mengajar melalui workshop secara online dengan berbantuan zoom meetings dan secara offline. Metode yang digunakan melibatkan workshop terstruktur dengan berbagai metode, seperti ceramah, demonstrasi, tanya jawab, dan latihan untuk menghasilkan karya tulis best practise guru dalam menggunakan teknologi pada pembelajaran. Hasil workshop ini mempunyai implikasi yang menarik untuk meningkatkan pemahaman guru IPA tentang penggunaan inovasi dalam pembelajaran.